1998
DOI: 10.1006/dbio.1998.8936
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Regulation of MuSK at the Neuromuscular Junction

Abstract: The receptor tyrosine kinase, MuSK, is required for the formation of the neuromuscular junction (NMJ) where MuSK becomes phosphorylated when exposed to neuronally synthesized isoforms of agrin. To understand better the mechanisms by which MuSK mediates the formation of the NMJ, we have examined how MuSK expression is regulated during development in the embryo, by neuromuscular injury in the adult and by agrin in vitro. Here we show that MuSK is associated with the earliest observable AChR clusters at the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 31 publications
9
58
0
1
Order By: Relevance
“…The localization of MuSK clusters in the γ -/-muscle was similar to that observed in the wildtype muscle (arrowheads in Fig. 8B,F), and consistent with the previously reported pattern of MuSK antibody staining in wild-type embryonic muscles (Bowen et al, 1998). Therefore, the phenotype developed in the γ -/-muscles is unlikely to be due to alternation of MuSK expression; instead, it probably resulted from the lack of the γ-subunit and consequently the absence of prepatterned AChRs (Fig.…”
Section: Clustering Of Musk In the Absence Of The γ-Subunitsupporting
confidence: 91%
See 1 more Smart Citation
“…The localization of MuSK clusters in the γ -/-muscle was similar to that observed in the wildtype muscle (arrowheads in Fig. 8B,F), and consistent with the previously reported pattern of MuSK antibody staining in wild-type embryonic muscles (Bowen et al, 1998). Therefore, the phenotype developed in the γ -/-muscles is unlikely to be due to alternation of MuSK expression; instead, it probably resulted from the lack of the γ-subunit and consequently the absence of prepatterned AChRs (Fig.…”
Section: Clustering Of Musk In the Absence Of The γ-Subunitsupporting
confidence: 91%
“…The samples were blocked in dilution buffer (500 mM NaCl, 0.01 M phosphate buffer, 3% BSA and 0.01% thimerosal), and then incubated with primary antibody-neurofilament 150 (Chemicon, Temecula, CA), rapsyn (Affinity Bioreagents, Golden, CO), synaptophysin (Dako, Carpinteria, CA), synaptic vesicle protein 2 (SV2) (Developmental Studies Hybridoma Bank, University of Iowa, Iowa City, IA), MuSK (41101K) (Bowen et al, 1998), synaptotagmin 2 or syntaxin (gifts from Dr Thomas Sudhof, UT Southwestern Medical Center, Dallas, TX). Muscles were then incubated with fluorescein isothiocyanateconjugated secondary antibodies and Texas Red-conjugated α-bungarotoxin (α-bgt) (10 -8 M, Molecular Probes).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…MuSK signaling depends on an autophosphorylated tyrosine residue in its juxtamembrane region (Y553) contained within an NPXY motif for which Dok7 is the only known binding partner and target (Fig. 5B) (8,30,59,71). This motif was recognized, to various affinities, by the Appl, Dok2, and ShcD PTB domains in the array-based screen (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AChRs aggregate and co-localize with a large number of other molecules [reviewed by Willmann and Fuhrer, 2002] in response to motor-neuron-derived agrin [reviewed by McMahan, 1990] through signaling events that require a muscle-specific kinase (MuSK) Sugiyama et al, 1997;Bowen et al, 1998;Gautam et al, 1999]. MuSK aggregates and co-localizes with AChRs [Fuhrer et al, 1997], is required for neuromuscular synapse formation and in the adult is found only at neuromuscular synapses [Valenzuela et al, 1995].…”
Section: Introductionmentioning
confidence: 99%